NILAI-NILAI PENDIDIKAN DALAM KALIMAT AZAN - H. Abdullah Syarif (STAI Hubbulwathan Duri, 2015)
The value of education in the sentence azan includes several elements, among others, first, the educational value of monotheism, instilling the values of monotheism to children who are expected to have strong beliefs, Aqidah to God alone and avoid shirk. Second, the educational value ubudiyah, which through the azan in children at birth is expected to be a child who always maintain the cleanliness, discipline, orderly, like helping others, not bothersome, always do good to others, do not do evil, be useful and beneficial for the people others, both in the life of society, nation, state and religion. Thirdly, the educational value akhlaqiyah, this value imparted to a newborn child so that the child has a good personality commendable to God, fellow human beings, as well as to animals and nature. And so the child can try, do the right path, but it does not spoil. Azan sentence submitted to a newborn child could be applied because of the wisdom and educational value contained in the sentence azan. Because, first received sound human hearing are sentences calls the Supreme Being that contains the greatness of God, is also the creed as a condition of the first to convert to Islam.